Enkelt företagande? En granskning av gränsbeloppsberäkningsförslagen i SOU 2024:36 Förenkla och förbättra - Melin,Karl (2024)
This thesis studies the special regulatory framework governing closely held companies and their shareholder taxation, and compares the applicable law with the proposals in SOU 2024:36 ‘Simplify and Improve’ (Förenkla och Förbättra). Closely held companies occupy a central role in the Swedish economy and employ many individuals. The existing system is difficult to navigate, creating unequal conditions for shareholders and potentially undermining the legitimacy and horizontal equity of the tax system. Through a legal dogmatic methodology, this thesis clarifies current law and analyses the committee’s proposals for a new threshold amount (gräns-belopp) calculation. Currently, the framework relies on two principal methods — the simplification rule and the main rule — demanding complex assessments and imposing substantial administrative burdens. SOU 2024:36 proposes merging them into a single model based on a base amount, a wagebased component, and interest on higher tax bases. By abolishing wage withdrawal and capital share requirements, the proposal aims to enable more shareholders, especially in smaller enterprises, to benefit more transparently. These proposals should significantly reduce administrative loads and discourage tax avoidance. They would also foster a more predictable system, strengthening legitimacy and neutrality. Although further simplifications could have been considered, the chosen balance promotes automation and practical implementation, aiding both shareholders and authorities. In conclusion, the proposals in SOU 2024:36 broadly align with the ambition to simplify and improve closely held company taxation. A more accessible and predictable regulatory framework may enhance legitimacy, efficiency, and entrepreneurship in Sweden.
Keywords: Skatterätt; Fåmansföretag; Gränsbelopp